Research on the Watchtower Architecture of Overseas Chinese Hometown in Tangjiawan, Zhuhai — Taking Huitong South Watchtowers and Huitong North Watchtowers as Examples - Junxin Song (PT FORMOSA CENDEKIA GLOBAL, 2022)
The architectural design of the watchtowers in the hometown of overseas Chinese in Tangjiawan was affected by social environmental factors and historical factors, which well adapted to the climate of the Tangjiawan area and formed a unique architectural style, representing the characteristics of history and culture at that time. This paper analyzes the architectural function, use function and architectural form of Huitong South watchtowers and Huitong North watchtowers, and preliminarily discusses the regional characteristics of watchtowers in the Tangjiawan hometown of overseas Chinese.